Serious Maricas and Their Male Concubines: Seeking Trans History and Intimacy in Argentine Police and Prison Records, 1921–1945. - Fernández-Galeano, Javier; Yarfitz, Mir (Hispanic American Historical Review, 2023)
State, legal, and medical experts in early twentieth-century Argentina conflated what would today be distinguished as same-sex attraction and trans or nonbinary gender experience. An urban subculture of self-styled maricas was pathologized by criminologists and occasionally targeted by police. Scholarship on these subjects has often focused on medical and cultural representation, situating maricas in the genealogy of homosexuality. This article brings insights from trans studies to several microhistories from police and prison archives in Rosario and Buenos Aires in order to focus on sociocultural practices. In their courtship rituals, romantic and sexual relationships, and household roles, Emilia, Dora, and La Lita engaged both respectability and sexual playfulness as modes of feminine expression.